Congenital dermal facial temporal sinus: Rare presentation of intraorbital dermoid in children - Nandita A Saxena; Akshay G Nair; Bharati K Kulkarni; Pooja M Multani; Hemant N Lahoti; Shyam S Borwankar; Dipesh Goel (Wolters Kluwer Medknow Publications, 2019)
We present a rare case of an intraorbital dermoid which was associated with a small temporal region dermal sinus in a 3-year-old child. This got infected and the child presented with orbital cellulitis. Definitive surgery involved excision of all the dermal elements using a superficial and intraorbital approach. We stress the need to evaluate, apparently benign lateral facial dermal sinuses as they may be the pointers of the underlying pathological deep dermoid cysts to avoid complications.